PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN, DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2009-2012 - Ahmad, Gatot Nazir; Sari, Leli Novita; Mardiyati, Umi (Fakultas Ekonomi, Universitas Negeri Jakarta, 2014)
The purpose of this study is to know the effect of institutional ownership, firm size and corporate governance on earnings management in manufacturing firm. The sample using purposive sampling. The research model in this study employs panel data analysis with random effect approach. The empirical results show that institutional ownership and firm size have negative and significant effect on earnings management, but the board of commissioners and the audit committee have negative and not significant on earnings management. Keywords: institutional ownership, firm size, corporate governance, the board of commissioners, audit committee, earnings management